Single cases from multiple perspectives: a qualitative study comparing the experiences of patients, patients' caregivers, surgeons, and nurses when bad news is delivered about cancer. Issue 3 (18th October 2020) - Matthews, Tamyra; Baken, Donald; Ross, Kirsty
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Qualitative literature on the experiences of those delivering and receiving bad news about cancer has revealed what these parties consider important during the process across many different patient cases. The current study aims to add to this understanding by employing a "linked case" study design to directly compare the perspectives of patients, their caregivers, and health care professionals (HCPs) involved in a series of single-patient cases of breaking bad news. Method: Semistructured interviews were conducted with 13 participants (5 patients, 4 caregivers, 2 surgeons, and 2 nurses) who formed 5 linked cases. Interviews were analyzed using interpretative phenomenological analysis and directly compared within each linked case. Results: Analyses identified 2 main superordinate themes. The first labeled "accurately perceiving and responding to needs, " included HCPs recognizing and responding to patients' and caregivers' individual emotional and informational needs. The second labeled "carers fulfilling necessary roles, " identified the various roles HCPs and patients' caregivers took to satisfactorily meet patients' needs. Conclusions: The findings suggest the importance of HCPs accurately perceiving and responding to patients' and caregivers' various needs and caregivers ability and willingness to fulfilling support roles in a way that aligns with their own resources and patients' needs. This highlights the value of HCPs developing and applying interpersonal skills within bad news encounters, working as a team, and exploring caregivers' resources for patient support.